Percutaneous Coronary Intervention versus Coronary Artery Bypass Grafting for Diabetics with Multivessel Coronary Artery Disease: The Korean Multicenter Revascularization Registry (KORR) - Gwon, Hyeon-Cheol (The Korean Academy of Medical Sciences, 2005)
This study was designed to assess the relative merits of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in multivessel coronary artery disease (MVCAD), particularly for Korean diabetics. Among 3,279 patients with MVCAD who were recommended for revascularization were enrolled from nine centers in Korea, 2,154 were selected after statistical adjustments for the disparities between two groups. Survival rates were not significantly different for three years between two groups. Among diabetic patients, the three-year mortality rate in PCI group was 1.9-fold higher than that of CABG group, although it was not statistically significant (PCI 19.8%, CABG 11.4%, p=0.14). The three-year mortality rate was similar between the two groups in non-diabetics (PCI 8.3%, CABG 10.0%, p=0.50). The 30-day rate of cerebrovascular event was higher in CABG group, for both diabetic (CABG 3.6%, PCI 0.0%, p<0.001) and non-diabetic patients (CABG 2.4%, PCI 0.0%, p<0.001). Short- and long-term revascularization rates were higher in PCI group than in CABG group. As a conclusion, this Korean registry demonstrates that PCI was associated with comparable survival rates and lower short-term morbidity, but a greater requirement for repeated revascularization compared with CABG in Korean diabetics.